Age‐incidence patterns of seminoma and nonseminoma among males and females in Germany and the United States, 2008–2016. (12th September 2022) - Stang, Andreas; Trocchi, Pietro; Kajüter, Hiltraud; Trabert, Britton; Oosterhuis, J. Wolter; McGlynn, Katherine A.
Abstract: Background & objectives: The comparison of the incidence of gonadal germ cell tumors among males and females can provide insights that cannot be gained by separately studying these tumors. Material and methods: Incidence data on male and female gonadal germ cell tumors were drawn from the cancer registries of North Rhine‐Westphalia, Germany, and the United States Surveillance, Epidemiology and End Results program, for non‐Hispanic White persons only, for the years 2008–2016. We estimated age‐standardized and age‐, and histology‐specific incidence rates. Results: We included 21, 840 male and 716 female gonadal germ cell tumors. Incidence rates among males were higher in Germany (95.8 per million, standard error [SE] 1.1) than in the United States (68.0, SE 0.6), while incidence rates among females were lower in Germany (1.9, SE 0.2) than in the United States (2.6, SE 0.1). The characteristic peak of infantile (age 0–4 years) germ cell tumors among males were missing among females. The age peak of ovarian germ cell tumors occurred 15–20 years earlier (Germany: 10–14 years, United States: 15–19 years) than the age peak of testicular germ cell tumors (30–34 years). The three most common testicular germ cell tumors histologies were seminoma, mixed germ cell tumors, and embryonal carcinoma Among females, the three most common ovarian germ cell tumors histologies were teratoma, yolk sac tumor, monodermal teratomas, and somatic‐type tumors arising from dermoid cysts in both countries. Discussion: The characteristic peak of infantile (age 0–4 years) germ cell tumors among males was missing among females. The shapes of the age‐specific incidence curves are similar for males and females in Germany and the United States, though with much lower incidence rates in females, suggesting a common pathogenesis. Conclusion: The lower rates among females may be due to the lower number of initiated tumors in the absence of the Y‐chromosome, and the earlier peak among females may be due to a younger age at puberty.